Pre-departure preparation and co-curricular activities for Students' intercultural exchange: A mixed-methods study. (April 2018) - Chan, E. Angela; Liu, Justina Yat Wa; Fung, Keith Hin Kee; Tsang, Pak Lik; Yuen, John
Abstract: Background: Nurses are required to be culturally competent to provide quality care to an increasingly diverse and ageing population. International exchange programmes were developed to support the traditional nursing curriculum. These programmes have often overlooked the importance of pre-departure preparation and co-curricular activities to the development of intercultural competency. Objectives: To explore the influence of pre-departure and co-curricular activities on the intercultural learning experiences of both exchange and host students in a short-term international summer programme. Design: A mixed-methods study. Setting: Students were recruited from international and mainland exchange partners, with host students as ambassadors. The international summer programme involved a week of online pre-departure activities and two weeks of face-to-face meetings. Participants: A convenience sample of 62 students from diverse cultural backgrounds was recruited on a voluntary basis. The participants were aged between 19 and 27. Methods: Data were collected from students' pre- and post-visit questionnaires, discussions within the workshops, their online discussion threads, and focus group discussions. Results: The quantitative findings suggested that students' cultural intelligence improved significantly after the exchange programme. Qualitatively, three themes emerged as: 1) Students' motivation to engage in intercultural learning; 2) Barriers to intercultural communication; 3) Enablers of intercultural communication. Conclusion: Pre-departure preparation enabled students to discuss their common goals and expectations, while exploring differences, asked for practical living information, and used the basic intercultural concepts in their discussion on the care of elderly. This virtual encounter has lay the foundation for students' subsequent discussions about the why and how the differences that inform their own practices and about global ageing and poverty issues during their co-curricular activities. While the pre-departure preparation could serve as a stimulus, the value of this programme for intercultural learning also rests with the importance of debriefing to further students' reflective and experiential learning. Highlights: Pre-departure preparation enhances students' motivation for intercultural learning. Co-curricular activities provide good intercultural learning opportunities. Careful facilitation is necessary if learning is to be maximized. Local/exchange student interactions on campus achieve internationalization at home. Short-term programmes can stimulate interest in further intercultural development.